Pengembangan Instrumen Tes Higher Order Thinking Skills (HOTS) Konten Perbandingan untuk Siswa Fase D - Nabilah, Ulfa; Armis, Armis; Saragih, Sehatta (Polinomial : Jurnal Pendidikan Matematika, 2026)
Higher Order Thinking Skills (HOTS) are essential competencies that students must possess. Many students still exhibit low levels of HOTS. This study aims to develop a Higher Order Thinking Skills (HOTS) instrument in comparison content for Phase D students. The research employed a development studies model consisting of two main stages: the preliminary stage and formative evaluation. The formative evaluation stage comprised several steps, including self-evaluation, expert review, one-to-one, small group, and field testing. The research subjects involved 30 Phase D students. Data were collected through validation sheets, student readability questionnaires, and HOTS test results, which were analyzed using Anates Uraian 4.0.5 software. The results indicated that the ten HOTS items developed met both rational and empirical validity criteria, showed very high reliability (0.95), had varying levels of difficulty (two easy, six moderate, and two difficult items), and demonstrated good discriminating power. Therefore, the developed HOTS instrument on comparison content is considered feasible to be used as an evaluation tool to enhance students’ critical, analytical, and creative thinking skills.